The study of EMG parameters of trans-tibial amputees for walking with different speeds / Ibtissam El Ghailassi - Ibtissam, El Ghailassi (2019)
The chief goal of the rehabilitation treatment is to ascertain the trans-tibial amputee can walk on top smoothly. The study aim was to determine the effects of the treadmill walking with three different speeds, on EMG parameters for the trans-tibial amputee and healthybodied. Wireless EMG sensors and treadmill instrument had used to fulfil the aim of this study. The investigation mission was to walk along the treadmill with three different speeds {2, 3 and 4 km/h}. Twelve subjects were contributory in this study, ten healthybodied and two unilateral trans-tibial amputees. EMG parameters had utilised to record EMG patterns of the above-knee muscles; rectus femoris muscle and biceps femoris muscle, during the walking activity on the treadmill at three different speeds. The results of EMG patterns had compared between the amputated limb and a sound limb. Healthybodied subjects demonstrated asymmetry EMG patterns in rectus femoris muscle and biceps femoris muscle during the walking speeds. While the trans-tibial amputee subjects had displayed symmetry EMG patterns amongst a sound leg and an amputated leg with little differences. Moreover, the results indicate the muscle activity was highly affected due to walking along the treadmill at three different speeds. EMG peak amplitude; wrists and biceps femoris muscles have demonstrated a highly notable impact across three different velocities. Due to subjects' conditions, since amputations, medication, stress and overweight considered factors affected the EMG patterns. Consequently, as the walking level in the trans-tibial amputee considers a significant functional requirement. We might employ the outcomes of this investigation to assist in the rehabilitation treatment of the trans-tibial amputee, by considering the distance and maximum speed while using the prosthesis.